2019
DOI: 10.3390/sports7040092
|View full text |Cite
|
Sign up to set email alerts
|

‘Perhaps a Bit Different to What We Did Twenty Years Ago’: Senior Teachers’ Perceptions of Outdoor Adventure within Primary Education in England

Abstract: Outdoor and adventurous activities (OAA) are now a compulsory component of the primary education curriculum in England, with senior leadership teams exerting significant influence on its delivery in schools. This study considers senior teachers’ perceptions and value of the OAA strand of the Physical Education (PE) National Curriculum (NC) in primary education. Six senior teachers from across a large northern city took part in semi-structured interviews. Data was analysed using an interpretivist paradigm incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(191 reference statements)
0
4
0
Order By: Relevance
“…This was also supported by the study of Umar and Yusoff ( 2014 ), who stated that senior teachers use ICT less than younger teachers. Additionally, from a broad perspective of analysis, it is considered interesting to pay attention to institutional support at the level of different education laws and the perception that contemporary legislation has regressed in terms of support for teachers, as reflected in the study by Webber and Hardwell ( 2019 ). This is in addition to encouraging school management to increase staff training and to develop their competencies, based on studies such as that developed by Abdul ( 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…This was also supported by the study of Umar and Yusoff ( 2014 ), who stated that senior teachers use ICT less than younger teachers. Additionally, from a broad perspective of analysis, it is considered interesting to pay attention to institutional support at the level of different education laws and the perception that contemporary legislation has regressed in terms of support for teachers, as reflected in the study by Webber and Hardwell ( 2019 ). This is in addition to encouraging school management to increase staff training and to develop their competencies, based on studies such as that developed by Abdul ( 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of green space and the outdoor context on health and wellbeing has also been investigated [61,62]. Contemporary research has shown that the nature, scope and potential value of adventure education goes way beyond the traditional notion of expected AEP outcomes, allowing for more extensive personal benefits and general health and wellbeing to be accrued [25,33,62,63].…”
Section: The Six Aep Elements In Contextmentioning
confidence: 99%
“…McKenzie suggested that outcomes were dependent on how well the interaction between each of these categories aligned with programme goals. Physical environment referred to the use of unfamiliar outdoor settings to facilitate new perspectives on everyday this has been compounded by the continued prevalence of packaged "off the shelf" outdoor and adventure delivery to schools through private organisations [25]. Outdoor environments continue to be sanitised, rationalised, commercialized and commodified [3,[24][25][26][27] through the addition of purpose-built parks and centres, designed to provide opportunities for activities such as skateboarding, mountain biking, skydiving, surfing, rafting and kayaking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation